Pengaruh Pelatihan Kerja dan Pengalaman Kerja terhadap Kinerja Karyawan Dimoderasi Lingkungan Kerja pada PT. Bank Sumut Kantor Pusat Medan - Sunaryo, Sunaryo; Pentana, Sopi; Handoko, Bagus; Damayanti, Welly (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of work training and work experience on employee performance with the work environment as a moderating variable at PT. North Sumatra Bank Medan Head Office. This type of research uses quantitative methods, with a sample of 219 employees, the data used is primary data by distributing questionnaires to a sample of 219 employees, and the statistical analysis technique used is the SEM (Structural Equation Modeling) analysis technique using Smartpls 4. From the research results This shows that job training on employee performance has a significant positive influence, work experience on employee performance has a significant positive influence, the work environment on employee performance has a significant positive influence, the work environment as a moderating variable on the influence of job training on employee performance is insignificantly negative and the environment work as a moderating variable on the influence of work experience on employee performance is positive and significant.